Excel maths early skills book 9: learning numbers to 99 - Dunbar, Bev (Oxford University Press Karachi, 2006)
"Excel Maths Early Skills Book 9: Learning Numbers to 99" guides young learners in recognizing and working with numbers up to 99 through engaging exercises and activities. The book focuses on counting, number patterns, and basic place value, helping to strengthen foundational math skills.